A global analysis of parenchyma tissue fractions in secondary xylem of seed plants. Issue 4 (9th November 2015) - Morris, Hugh; Plavcová, Lenka; Cvecko, Patrick; Fichtler, Esther; Gillingham, Mark A. F.; Martínez‐Cabrera, Hugo I.; McGlinn, Daniel J.; Wheeler, Elisabeth; Zheng, Jingming; Ziemińska, Kasia; Jansen, Steven
Summary: Parenchyma is an important tissue in secondary xylem of seed plants, with functions ranging from storage to defence and with effects on the physical and mechanical properties of wood. Currently, we lack a large‐scale quantitative analysis of ray parenchyma (RP) and axial parenchyma (AP) tissue fractions. Here, we use data from the literature on AP and RP fractions to investigate the potential relationships of climate and growth form with total ray and axial parenchyma fractions (RAP). We found a 29‐fold variation in RAP fraction, which was more strongly related to temperature than with precipitation. Stem succulents had the highest RAP values (mean ± SD: 70.2 ± 22.0%), followed by lianas (50.1 ± 16.3%), angiosperm trees and shrubs (26.3 ± 12.4%), and conifers (7.6 ± 2.6%). Differences in RAP fraction between temperate and tropical angiosperm trees (21.1 ± 7.9% vs 36.2 ± 13.4%, respectively) are due to differences in the AP fraction, which is typically three times higher in tropical than in temperate trees, but not in RP fraction. Our results illustrate that both temperature and growth form are important drivers of RAP fractions. These findings should help pave the way to better understand the various functions of RAP in plants.